Effects of Temporary Functional Deafferentation in Chronic Stroke Patients: Who Profits More? - Elisabeth Sens; Marcel Franz; Christoph Preul; Winfried Meissner; Otto W. Witte; Wolfgang H. R. Miltner; Thomas Weiss (Neural Plasticity)
Temporary functional deafferentation (TFD) by an anesthetic cream on the stroke-affected forearm was shown to improve sensorimotor abilities of stroke patients. The present study investigated different predictors for sensorimotor improvements during TFD and indicated outcome differences between patients grouped in subcortical lesions only and lesions with any cortical involvement. Thirty-four chronic stroke patients were temporarily deafferented on the more affected forearm by an anesthetic cream. Somatosensory performance was assessed using von Frey Hair and grating orientation task; motor performance was assessed by a shape-sorter-drum task. Seven potential predictors were entered into three linear multiple regression models. Furthermore, effects of TFD on outcome variables for the two groups (cortical versus subcortical lesion) were compared. Sex and sensory deficit were significant predictors for changes in motor function while age accounted for changes in grating orienting task. Males, patients with a stronger sensory deficit, and older patients profited more. None of the potential predictors made significant contributions to changes in threshold for touch. Furthermore, there were no differences in sensorimotor improvement between lesion site groups. The effects of TFD together with the low predictability of the investigated parameters suggest that characteristics of patients alone are not suitable to exclude some patients from TFD.